For example:
Simplify: \(3x+5y+2y+3x\)
First, arrange the like terms together.
\(3x+3x+5y+2y\)
Now, take the common variables out
\(3x(1+1)+y (5+2)\)
\(= 3x(2)+y(7)\)
\(=6x+7y\)
For example:
Simplify: \(5y-3x-2x-y\)
First, arrange the like terms together.
\(5y-y-3x-2x\)
Now, take the common variables out.
\(y(5-1)+x(-3-2)\)
\(= y (4)+x(-5)\)
\(=4y-5x\)
Here, we will learn to simplify the expressions involving multiplication.
For example:
Simplify: \(4×a×a×b×2×c×b\)
Here, we will multiply the numbers and count the number of times each variable is multiplied by itself and write it as the power of that variable i.e.
\(4×a×a×b×2×c×b\)
\(= 4 ×2×a×a×b×b×c\)
\(= 8a^2b^2c\)
For example:
Simplify: \(\dfrac{16×a×b×a×b×c}{2×c×a×b×8}\)
In such type of expressions, we can cancel out the same variables appearing in both numerator and denominator i.e.,
\(\dfrac{16×a× \not{a}× \not{b}×b× \not{c}}{2×8× \not{a}× \not{b}× \not{c}}\)
\(=ab\)
A \(10mn^2p^2\)
B \(2mn^2p\)
C \(m^3np\)
D \(mn^2\)